2014
DOI: 10.1128/jvi.00534-14
|View full text |Cite
|
Sign up to set email alerts
|

Crucial Roles of Interleukin-7 in the Development of T Follicular Helper Cells and in the Induction of Humoral Immunity

Abstract: Interleukin-7 (IL-7) is a heavily glycosylated cytokine with a molecular mass of 25 kDa, and it is a member of the common ␥-chain receptor (CD132) cytokine family. IL-7 is secreted mainly by nonhematopoietic cells, such as thymic and intestinal epithelial cells, bone marrow stromal cells, keratinocytes, and reticular cells (1, 2). The receptor for IL-7, comprised of IL-7 receptor alpha (IL-7R␣; CD127) and the common ␥ chain, is expressed on various immune cells, including immature B cells, early thymocyte prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
59
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 49 publications
(54 reference statements)
0
59
0
1
Order By: Relevance
“…Because a previous report suggested that IL-7 facilitates the generation of Tfh cells (17), the induction of Tfh cells post-rRABV immunization was investigated. BALB/c mice (n ϭ 3) were intramuscularly (i.m.)…”
Section: Construction and Characterization Of Recombinant Rabv-expresmentioning
confidence: 99%
See 2 more Smart Citations
“…Because a previous report suggested that IL-7 facilitates the generation of Tfh cells (17), the induction of Tfh cells post-rRABV immunization was investigated. BALB/c mice (n ϭ 3) were intramuscularly (i.m.)…”
Section: Construction and Characterization Of Recombinant Rabv-expresmentioning
confidence: 99%
“…Because Tfh cells directly associate with GC B cells (17), the effect of IL-7 expressed by rRABV on GC B cells was evaluated. The inguinal LNs were collected at 7 and 14 dpi from BALB/c mice (n ϭ 3) that were individually immunized with 10 6 FFU of one of the rRABVs or with DMEM alone.…”
Section: Construction and Characterization Of Recombinant Rabv-expresmentioning
confidence: 99%
See 1 more Smart Citation
“…IL-7 is known to induce expansion of T cells under lymphopenic conditions (24). In our previous studies, we demonstrated that IL-7 can be used as a vaccine adjuvant to augment antigen-specific T cell response (25,26) and to enhance antibody responses through the induction of follicular helper T cells (27). Here, we demonstrate that a single intranasal pretreatment with Fc-fused IL-7 (IL-7-mFc), but not a native form of IL-7, completely protects mice from IAV-induced mortality for an extended period of time, even without preexisting IAV-specific immunity.…”
mentioning
confidence: 99%
“…S1. Chinese hamster ovary (CHO) cells were stably transfected with a plasmid encoding IL7-Fc or G-CSF-Fc, and proteins were prepared as described previously (29). Recombinant human IL7 (rIL7), purified from HEK 293E cells, was purchased from BioLegend.…”
Section: Preparation and Treatmentmentioning
confidence: 99%